Diffusion of Innovation within Informality: Social Capital in Agricultural Development of Indonesian Villages - Dewi Sawitri Tjokropandojo; Dika Fajri Fiisabiilillah; Fikri Zul Fahmi (The Directorate for Research and Innovation, Institut Teknologi Bandung, 2024)
This paper aims to investigate the extent to which social capital catalyzes the diffusion of innovation in agricultural communities. This study uses a qualitative approach in investigating two cases of horticultural producers in Cisondari and Cibodas, West Java, Indonesia. Our findings show that the presence of social capital (trust, networks, and norms) is considerably weak in both cases. Farmers have built networks and trust (which are implicated in mutual norms) for years but its success in developing their agricultural sectors is not evident. The social capital is strong enough to drive the diffusion of innovations but it is not (yet) able to create new innovative ideas. However, we found that social capital is able to drive the dissemination process of innovations without the presence of formal organizations, even though there are some limitations in its process. The findings of this paper have important implications for policy, especially in the development of innovation strategies for the agricultural sector in developing countries, such as Indonesia.